DOP37 Vedolizumab-induced endoscopic remission in anti-TNF exposed and anti-TNF naïve IBD patients: a large single-centre experience. (25th January 2019) - Verstockt, B; Mertens, E; Outtier, A; Van Assche, G; Vermeire, S; Ferrante, M
Abstract: Background: Vedolizumab (VDZ), a gut-focussed biological agent targeting α4β7 and hence preventing leukocyte trafficking into the intestinal wall, has demonstrated efficacy and safety in patients with Crohn's disease (CD) and ulcerative colitis (UC). Real-life endoscopic remission data are still very limited, especially in anti-TNF naïve patients. The present study compared VDZ-induced endoscopic outcome in anti-TNF naïve and exposed patients. Methods: We retrospectively assessed the medical charts of all IBD patients ( n = 408) who initiated VDZ therapy at our tertiary referral centre after the pivotal clinical trials, from January 2015 till April 2018, and who had a minimal follow-up of 6 months at our centre. Patients with an ostomy ( n = 11) or ileoanal pouch ( n = 20), as well patients without active disease ( n = 41) at start were excluded from the analysis. All patients received VDZ 300 mg IV at Week 0, 2, 6, and q8w thereafter. CD patients received an additional dosage at Week 10. Endoscopic remission was defined as a Mayo endoscopic subscore ≤1 at Week 14 (as per national reimbursement criteria) for UC, and absence of ulcerations at month 6 for CD. All endoscopies were performed by the same 3 IBD staff members. Non-responder imputation was applied for patients discontinuing VDZ prior to the endoscopic endpoint. Results: Of the 336 patients included (53.3% CD, 46.7% UC), 80.1% had been exposed to at least one anti-TNF agent (37.2% one, 39.0% two, 3.9% three anti-TNF agents), with endoscopic outcome available in 96.1% of patients. After a median (IQR) of 14.0 (13.6–14.6) weeks, 56.4% of UC patients achieved endoscopic remission, whereas 41.9% of CD patients experienced endoscopic remission after 22.1 (21.6–25.0) weeks (L2 (62.5%) vs. L1+L3 (38.5%), p = 0.03). No difference in disease duration could be found between remitters and non-remitters ( p = 0.70). Significantly more anti-TNF naïve vs. exposed patients achieved endoscopic remission (OR 2.9, Figure 1). Figure 1. Percentage of patients achieving endoscopic remission, compared between anti-TNF naive and anti-TNF exposed patients. No difference in remission rates was observed between patients failing 1 vs. ≥2 anti-TNF agents ( p = 0.26). Similarly, no effect of corticosteroids or immunomodulators during induction could be observed with regard to endoscopic remission ( p = 0.61, p = 0.86 respectively). Conclusions: This is the biggest, real-life, single-centre cohort study confirming that VDZ can induce endoscopic remission in both CD and UC patients, without any effect of concomitant therapy during induction. Although anti-TNF naive patients had a significantly better outcome, 44% of anti-TNF exposed patients did achieve endoscopic remission.